Prenatal Diagnosis of Holt–Oram Syndrome With a Novel Mutation of TBX5 Gene: A Case Report - He, Guan-nan; Wang, Xue-yan; Kang, Min; Chen, Xi-min; Xi, Na; Zhao, Jing; Chen, Xi (Frontiers in Pediatrics, 2021)
Background: Holt-Oram syndrome (HOS) is an autosomal dominant disorder caused by mutations of the TBX5 gene. Case presentation: We report a fetus with HOS diagnosed sonographically at 23 weeks of gestation. The fetal parents are non-consanguineous. The fetus exhibited radius and ulna short, hands pronate, right thumb not shown, and heart ventricular septal defect (VSD), while the fetal father exhibited VSD, and short radius and ulna only. Fetal brother had cubitus valgus and thumb adduction, except for VSD, the short radius and ulna. Whole exome sequencing (WES) revealed a novel mutation in the TBX5 (c.510+1G>A) in the fetus, inheriting from the father. The variant (c.510+1G>A), that occurs at splice donor and likely alters TBX5 gene function through impact on splicing, has no reported previously in China. Conclusion: Our case reported a novel variant in TBX5, which expanded the known genetic variants associated with Holt-Oram syndrome.